CeO2-MnOx superfine nanofiber catalyst as well as electrostatic spinning preparation method and application thereof

The CeO2-MnOx ultrafine nanofiber catalyst prepared by electrospinning technology solves the problems of low NOx removal efficiency and insufficient anti-toxicity in ultra-low temperature flue gas, and achieves efficient NOx removal and long-life catalyst performance.

CN119549143APending Publication Date: 2025-03-04JIANGSU UNIV OF SCI & TECH

Patent Information

Application Number
CN202411225878.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove NOx in industrial flue gas under ultra-low temperature conditions, and there is a problem of insufficient anti-toxicity, especially in flue gases containing interfering components such as SO2.

Method used

CeO2-MnOx ultrafine nanofiber catalyst is synthesized through electrospinning technology. This catalyst has a large specific surface area, rich active sites and excellent redox properties, and is suitable for ultra-low temperature flue gas denitrogenation.

Benefits of technology

The NOx conversion rate reaches more than 95% under ultra-low temperature conditions of 75-225℃, and the denitrification efficiency of more than 90% under high SO2 content of 100℃ is achieved, which extends the service life of the catalyst and reduces the cost of industrial denitrification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549143A_ABST
    Figure CN119549143A_ABST
Patent Text Reader

Abstract

The invention discloses a CeO2-MnOx superfine nanofiber catalyst as well as an electrostatic spinning preparation method and application thereof, and belongs to the technical field of material preparation and environmental protection. N-N dimethylformamide (DMF) is adopted as a solvent, cerium nitrate hexahydrate and manganese acetate tetrahydrate are adopted as precursor salts, polyvinylpyrrolidone (PVP) is adopted as a flocculating agent, a gelatinous precursor solution is formed, jet stretching is performed under the high-voltage electrostatic effect, a nanofiber membrane is obtained at the collecting end, and after drying, the CeO2-MnOx superfine nanofiber is obtained through calcination of a stepped heating program. The diameter of the catalyst is 300-400 nm, the catalyst has good oxidation reduction capacity, by means of the efficient electron transfer capacity of the nanofiber morphology and the confinement effect of a fiber cavity, the catalyst shows excellent ultralow-temperature denitration activity and sulfur resistance, denitration reaction is carried out within the temperature range of 75-225 DEG C, the NO conversion rate can be 95% or above, and the catalyst has the advantages of being low in cost and high in efficiency. The catalyst can be applied to the field of flue gas ammonia selective catalytic denitration in non-power industry, and has a good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ultra-low temperature industrial flue gas denitration catalysts, and in particular to a CeO2-MnO x Ultrafine nanofiber catalyst and its electrospinning preparation method and application. Background Art

[0003] NH3 selective catalytic reduction (NH3-SCR) is currently an efficient, economical and practical denitrification method. However, compared with coal-fired power plants, the flue gas temperature in non-power industries is mostly below 250°C. Secondly, the composition of these industrial tail gases is complex, usually containing a large number of interfering components such as SO2, alkali metals, Hg and Pd that poison the catalyst, making it difficult for the current commercial SCR catalyst to operate stably under real working conditions. In order to make NH3-SCR technology applicable to flue gas denitrification in different industries, the flue gas needs to be pretreated for dust removal and desulfurization, but the temperature of the pretreated flue gas is mostly below 150°C or even lower. Therefore, it is of great significance to study a denitrification catalyst with excellent NO elimination efficiency and certain anti-poisoning ability in the ultra-low temperature section (<150°C). Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention aims to provide a CeO2-MnO x Ultrafine nanofiber catalyst and its electrostatic spinning preparation method and application. The present invention synthesizes CeO2-MnO by electrostatic spinning technology. x Ultrafine nanofiber catalyst, the obtained CeO2-MnO x Ultrafine nanofiber catalysts have the advantages of large specific surface area, rich active sites, a large number of independent cavities and excellent redox properties. When used in industrial flue gas denitrification, they not only effectively reduce the working temperature of the flue gas denitrification catalyst and reduce additional energy consumption, but also have excellent denitrification activity and strong sulfur resistance in the ultra-low temperature section, effectively avoiding the deactivation effect of high-temperature and high-sulfur flue gas on the catalyst, extending the service life of the catalyst, thereby reducing the cost of industrial denitrification, and have good application prospects.

[0005] In order to solve the problems of the prior art, the technical solution adopted by the present invention is as follows:

[0006] A CeO2-MnO x The electrospinning preparation method of ultrafine nanofiber catalyst comprises the following steps:

[0007] Step 1, preparation of spinning precursor solution:

[0008] First, cerium nitrate hexahydrate and manganese acetate tetrahydrate are dissolved in DMF, and after sufficient stirring, polyvinyl pyrrolidone (PVP) is slowly added, and the mixture is sealed and stirred at room temperature to form a gel precursor solution, wherein the molar ratio of Ce / Mn is 3:7-7:3, and the mass fraction of polyvinyl pyrrolidone is 7%-9%;

[0009] Step 2, preparation of nanofiber membrane by electrospinning:

[0010] Electrospinning the gel precursor solution to obtain a spinning membrane;

[0011] Step 3, spinning heat treatment:

[0012] The spun film was dried in a vacuum drying oven and calcined at high temperature to obtain CeO2-MnO x Ultrafine nanofiber catalyst.

[0013] As an improvement, the polyvinyl pyrrolidone in step 1 is K81-K98, and the average molecular weight is 1,300,000.

[0014] As an improvement, the stirring rate in step 1 is 1500-2000 rpm, and the stirring time is 8-18 h.

[0015] As an improvement, the process parameters of the electrospinning in step 2 are: a medical syringe and a polytetrafluoroethylene Luer needle are connected to a polytetrafluoroethylene tube as a spinning head, the drum receiver speed is 350-420rpm, the vertical distance from the nozzle to the receiver is 15-20cm, the spinning voltage is 15-20kV, and the propulsion rate is 0.5-0.6mL / h.

[0016] As an improvement, the drying temperature in step 3 is 60-80°C and the drying time is 6-12 hours.

[0017] As an improvement, the high temperature calcination in step 3 is carried out in stages in a muffle furnace under air atmosphere, wherein the first stage calcination temperature is 200°C for 2 hours, and the second stage calcination temperature is 400-600°C.

[0018] As an improvement, in step 3, the heating rate of the first stage of calcination is 2°C / min, and the heating rate of the second stage of calcination is 5°C / min.

[0019] The CeO2-MnO prepared by the above preparation method x Ultrafine nanofiber catalyst with a diameter of 300-400nm.

[0020] The above CeO2-MnO xThe application of ultrafine nanofiber catalysts in ultra-low temperature flue gas denitrification in non-electricity industries has the following specific steps: in ultra-low temperature flue gas at 75-225°C, ammonia is used as a reducing agent to selectively reduce NO in the flue gas to nitrogen (N2), and the efficiency of NH3-SCR reaction catalytic elimination of nitrogen oxides reaches more than 95%. At the same time, at 100°C and containing 40ppm SO2 in flue gas, the conversion efficiency of nitrogen oxides reaches 90%.

[0021] The present invention combines the technical problems currently faced by flue gas denitrification in the non-electric industry, integrates the unique performance of metal Mn in NH3-SCR reaction and the excellent oxygen storage and release function and electron transfer ability of metal Ce, and synthesizes CeO2-MnO by electrospinning technology. x Ultrafine nanofibers are used in the ultra-low temperature denitrification field of non-electrical industries. CeO2-MnO prepared by electrospinning x The ultrafine nanofiber denitrification catalyst exposes more active sites, and its unique nanofiber morphology also helps to improve the catalyst's ability to resist sulfur poisoning. Tests have shown that the CeO2-MnO x The ultrafine nanofibers undergo denitration reaction in the temperature range of 75-225°C, and the NO conversion rate can reach more than 95%. In addition, the catalyst of the present invention also exhibits excellent anti-sulfur poisoning performance at 100°C, ensuring that the catalyst is effective in NO removal from flue gas in non-power industries. x It has good application prospects in emission control.

[0022] Beneficial effects:

[0023] Compared with the prior art, the present invention provides a CeO2-MnO x Ultrafine nanofiber catalyst and its electrospinning preparation method and application have the following advantages:

[0024] 1. CeO2-MnO prepared by electrospinning technology x Ultrafine nanofibers, with a fiber diameter of 300-400nm, have evenly distributed active components and a stable structure, providing abundant active sites for the denitrification reaction.

[0025] 2. CeO2-MnO x Ultrafine nanofiber catalysts have excellent ultra-low temperature denitrification activity. Tests show that in ultra-low temperature flue gas at 75-225°C, ammonia is used as a reducing agent to selectively reduce NO in the flue gas to nitrogen, and the efficiency of the reaction catalytic elimination of nitrogen oxides reaches more than 95%;

[0026] 3. CeO2-MnO xUltrafine nanofiber catalyst has good low-temperature sulfur poisoning resistance and achieves a denitrification efficiency of more than 90% in 100°C flue gas containing 40ppm SO2. Applied in industrial production, it effectively avoids the deactivation of catalysts by sulfur dioxide, thereby extending the service life of the catalyst and reducing industrial denitrification costs.

[0027] 4. The cerium and manganese elements and other reaction raw materials used in the preparation of the present invention are environmentally friendly, abundant in resources, cheap and easy to obtain, which effectively reduces the production cost and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The CeO2-MnO prepared in Example 2 of the present invention x SEM images of ultrafine nanofibers, where the scale bar in (a) is 2 μm and the scale bar in (b) is 3 μm.

[0029] Figure 2 CeO2-MnO at different calcination temperatures x XRD results of ultrafine nanofibers.

[0030] Figure 3 CeO2-MnO at different calcination temperatures x H2-TPR results of ultrafine nanofibers.

[0031] Figure 4 CeO2-MnO prepared by different processes x NH3-SCR results of ultrafine nanofiber catalysts, where (a) is different Ce / Mn molar ratios and (b) is different calcination temperatures.

[0032] Figure 5 CeO2-MnO prepared by different processes x The sulfur resistance test results of the ultrafine nanofiber catalyst are as follows: the test temperature is 100°C, the SO2 content is 40 ppm, where (a) is different Ce / Mn molar ratios, and (b) is different calcination temperatures. Specific implementation methods

[0034] Example 1

[0035] Accurately weigh 3.4738 g of cerium nitrate hexahydrate and dissolve it in 20 mL of DMF. Stir until dissolved. Accurately weigh 1.9600 g of manganese acetate tetrahydrate and add it to the above solution. Stir thoroughly for 30 min. Add 2.0000 g of PVP and stir at room temperature for 12 h to form a gel precursor solution.

[0036] The precursor solution was sucked into the syringe and fixed on the propeller for electrospinning. The vertical distance from the nozzle to the roller receiver was 18 cm, the spinning voltage was set to 20 kV, and the propulsion rate was set to 0.6 mL / h to obtain a spinning membrane.

[0037] The spun membrane was dried at 60 °C in a vacuum drying oven for 12 h, then heated to 200 °C at a rate of 2 °C / min in air atmosphere, kept warm for 2 h, and then heated to 400 °C at a rate of 5 °C / min, kept warm for 4 h to obtain CeO2-MnO x Ultrafine nanofiber catalyst, abbreviated as Ce1Mn1-400.

[0038] Example 2

[0039] The second calcination temperature in Example 1 was changed to 500°C, and the remaining steps were the same as in Example 1 to obtain CeO2-MnO x Ultrafine nanofiber catalyst, abbreviated as Ce1Mn1-500.

[0040] Example 3

[0041] The second calcination temperature in Example 1 was changed to 600°C, and the remaining steps were the same as in Example 1 to obtain CeO2-MnO x Ultrafine nanofiber catalyst, abbreviated as Ce1Mn1-600.

[0042] The Ce1Mn1-T catalysts prepared by the present invention (second stage calcination temperature T = 400 ° C, 500 ° C, 600 ° C) were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), programmed temperature reduction (H2-TPR) and catalytic performance testing. The morphology, crystal structure, reducibility, catalytic activity and sulfur resistance of the catalysts prepared in Examples 1 to 3 were evaluated and analyzed. The results are as follows Figure 1-3 shown.

[0043] from Figure 1 It can be seen that the fiber surface of the Ce1Mn1-500 catalyst of the present invention is smooth, the fiber diameter is uniform, and the size is 300-400nm, the fiber structure is continuous and uniform, and there is no breakage.

[0044] from Figure 2 It can be seen from XRD that the characteristic diffraction peak of CeO2 cubic fluorite structure becomes sharper with the increase of the maximum calcination temperature.

[0045] from Figure 3 It can be seen that with the increase of the maximum calcination temperature, the reducibility of the catalyst weakens.

[0046] Comparative Example 1

[0047] Accurately weigh 1.9540 g of cerium nitrate hexahydrate and dissolve it in 20 mL of DMF. Stir until dissolved. Accurately weigh 2.5725 g of manganese acetate tetrahydrate and add it to the above solution. Stir thoroughly for 30 min. Add 2.0000 g of PVP and stir at room temperature for 12 h to form a gel precursor solution.

[0048] The precursor solution was sucked into the syringe and fixed on the propeller for electrospinning. The vertical distance from the nozzle to the roller receiver was 18 cm, the spinning voltage was set to 20 kV, and the propulsion rate was set to 0.6 mL / h to obtain a spinning membrane.

[0049] The spun membrane was dried in a vacuum drying oven at 60 °C for 12 h, then heated to 200 °C at a rate of 2 °C / min in air atmosphere, kept warm for 2 h, and then heated to 500 °C at a rate of 5 °C / min and kept warm for 4 h to obtain CeO2-MnO x Ultrafine nanofiber catalyst, abbreviated as Ce3Mn7-500.

[0050] Comparative Example 2

[0051] Accurately weigh 3.6475 g of cerium nitrate hexahydrate and dissolve it in 20 mL of DMF. Stir until dissolved. Accurately weigh 0.8820 g of manganese acetate tetrahydrate and add it to the above solution. Stir thoroughly for 30 min. Add 2.0000 g of PVP and stir at room temperature for 12 h to form a gel precursor solution.

[0052] The precursor solution was sucked into the syringe and fixed on the propeller for electrospinning. The vertical distance from the nozzle to the roller receiver was 18 cm, the spinning voltage was set to 20 kV, and the propulsion rate was set to 0.6 mL / h to obtain a spinning membrane.

[0053] The spun membrane was dried in a vacuum drying oven at 60 °C for 12 h, then heated to 200 °C at a rate of 2 °C / min in air atmosphere, kept warm for 2 h, and then heated to 500 °C at a rate of 5 °C / min and kept warm for 4 h to obtain CeO2-MnO x Ultrafine nanofiber catalyst, abbreviated as Ce7Mn3-500.

[0054] The catalytic performance of Example 2, Comparative Example 1 and Comparative Example 2 was tested for NH3-SCR reaction. The specific reaction conditions are as follows: The catalytic reaction test was carried out in a fixed bed continuous flow quartz reactor. The catalyst particle size was 60-80 mesh and the dosage was 200 mg. The reaction gas composition was: 500 ppm NO, 500 ppm NH3, 200 ppm SO2, 5% O2, N2 as the balance gas, and the gas space velocity in the reaction was 40000 mL g -1 ·h -1Before the reaction, the catalyst was purged with high-purity N2 at 200°C for 30 minutes, and the catalytic reaction was carried out at 50-250°C. The activity data was collected after the reaction reached equilibrium. The product was detected and analyzed by FGA10 flue gas analyzer, and the NO conversion rate was calculated by the following formula:

[0055]

[0056] Through the above reaction test, the results are as follows Figure 4 and Figure 5 shown.

[0057] from Figure 4 As can be seen from (a), at the same calcination temperature, among the different Ce / Mn molar ratios, only when the molar ratio is 1:1, the NH3-SCR of the catalyst is the best, and a NO conversion rate of nearly 100% can be achieved at 75°C. At the same time, the NO conversion rate is more than 90% in the temperature range of 75-225°C.

[0058] from Figure 4 As can be seen from (b), when the calcination temperature is 500°C, the NH3-SCR activity of the catalyst is the best, with a NO removal efficiency of more than 95% in the range of 75-225°C.

[0059] from Figure 5 As can be seen from (a), at the same calcination temperature, the sulfur resistance of catalysts with different Ce / Mn molar ratios is different. The sulfur resistance of catalysts with Ce / Mn molar ratios of 7:3 and 1:1 is better than that of catalysts with Ce / Mn molar ratio of 3:7. They show similar sulfur resistance at 100°C, and the NO conversion rate can reach more than 95% in flue gas containing 40ppm SO2.

[0060] from Figure 5 As can be seen in (b), when the calcination temperature is 500°C, the catalyst has the best sulfur resistance. Under the test conditions of 100°C and 40ppm SO2, it exhibits a NO removal efficiency of more than 95%.

[0061] Tests have shown that the Ce1Mn1-500 catalyst exhibits excellent low-temperature denitrification activity and resistance to SO2 poisoning, achieving a NO conversion rate of more than 95% in the temperature range of 75-225°C. At the same time, the catalyst also exhibits excellent resistance to sulfur poisoning at 100°C.

[0062] In summary, the present invention combines the unique performance of metal Mn in NH3-SCR reaction and the excellent oxygen storage and release function and electron transfer ability of metal Ce, and synthesizes CeO2-MnO by electrospinning technology. x Ultrafine nanofibers are used in the ultra-low temperature denitrification field of non-electricity industry.x Ultrafine nanofiber denitrification catalysts expose more active sites. At the same time, their unique nanofiber morphology also helps to improve the catalyst's ability to resist sulfur poisoning. x It has good application prospects in emission control.

[0063] The present invention and its embodiments are described schematically above, and the description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and designs a structural method and an embodiment similar to the technical solution without creativity without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. A CeO2-MnO x The electrospinning preparation method of ultrafine nanofiber catalyst is characterized in that: The following steps are included: Step 1, preparation of spinning precursor solution: First, cerium nitrate hexahydrate and manganese acetate tetrahydrate are dissolved in DMF, and after sufficient stirring, polyvinyl pyrrolidone (PVP) is slowly added, and the mixture is sealed and stirred at room temperature to form a gel precursor solution, wherein the molar ratio of Ce / Mn is 3:7-7:3, and the mass fraction of polyvinyl pyrrolidone is 7%-9%; Step 2, preparation of nanofiber membrane by electrospinning: Electrospinning the gel precursor solution to obtain a spinning membrane; Step 3, spinning heat treatment: The spun film was dried in a vacuum drying oven and calcined at high temperature to obtain CeO2-MnO x Ultrafine nanofiber catalyst.

2. A CeO2-MnO according to claim 1 x The electrospinning preparation method of ultrafine nanofiber catalyst is characterized in that: The polyvinyl pyrrolidone in step 1 is K81-K98, and the average molecular weight is 1300000.

3. A CeO2-MnO according to claim 1 x The electrospinning preparation method of ultrafine nanofiber catalyst is characterized in that: The stirring rate in step 1 is 1500-2000 rpm, and the stirring time is 8-18 hours.

4. A CeO2-MnO according to claim 1 x The electrospinning preparation method of ultrafine nanofiber catalyst is characterized in that: The process parameters of the electrospinning in step 2 are: a medical syringe and a polytetrafluoroethylene Luer needle connected to a polytetrafluoroethylene tube are used as a spinning head, the rotation speed of the drum receiver is 350-420rpm, the vertical distance from the nozzle to the receiver is 15-20cm, the spinning voltage is 15-20kV, and the propulsion rate is 0.5-0.6mL / h.

5. A CeO2-MnO according to claim 1 x The electrospinning preparation method of ultrafine nanofiber catalyst is characterized in that: The drying temperature in step 3 is 60-80° C. and the drying time is 6-12 hours.

6. A CeO2-MnO according to claim 1 x The electrospinning preparation method of ultrafine nanofiber catalyst is characterized in that: The high temperature calcination in step 3 is carried out in stages in a muffle furnace under air atmosphere, wherein the first stage calcination temperature is 200° C. for 2 hours, and the second stage calcination temperature is 400-600° C.

7. A CeO2-MnO according to claim 1 x The electrospinning preparation method of ultrafine nanofiber catalyst is characterized in that: In step 3, the heating rate of the first stage of calcination is 2°C / min, and the heating rate of the second stage of calcination is 5°C / min.

8. CeO2-MnO prepared by any one of the preparation methods described in claims 1-7 x Ultrafine nanofiber catalyst, characterized in that The CeO2-MnO x The diameter of the ultrafine nanofiber catalyst is 300-400nm.

9. CeO2-MnO according to claim 8 x Application of ultrafine nanofiber catalysts in ultra-low temperature flue gas denitrification in non-electricity industries.

10. The use according to claim 9, characterized in that: The specific steps are: in ultra-low temperature flue gas at 75-225℃, ammonia is used as a reducing agent to selectively reduce NO in the flue gas to nitrogen (N2), and the efficiency of catalytic elimination of nitrogen oxides by NH3-SCR reaction reaches more than 95%. At the same time, in flue gas at 100℃ with a SO2 content of 40ppm, the conversion efficiency of nitrogen oxides reaches 90%.

Citation Information

Patent Citations

  • Catalyst for SCR denitration in boiler low-temperature fume and preparation method thereof

    CN101011659A

  • Preparation method of metal or metal oxide particle-containing CeO2 fiber catalyst

    CN104707604A

  • Preparation method of manganese oxide / cerium dioxide catalyst with hollow nano-fiber structure as well as product and application thereof

    CN107790121A

Cited By

  • Micron fiber low-temperature rare earth-based denitration catalyst and preparation method thereof

    CN120325291A

  • Micron fiber low-temperature rare earth-based denitration catalyst and preparation method thereof

    CN120325291B